Root Morphogenesis of Arabidopsis thaliana Tuned by Plant Growth-Promoting Streptomyces Isolated From Root-Associated Soil of Artemisia annua - Fu, Wenbo; Pan, Yanshuo; Shi, Yuhua; Chen, Jieyin; Gong, Daozhi; Li, Yuzhong; Hao, Guangfei; Han, Dongfei (Frontiers in Plant Science, 2022)
In this study, the capacity to tune root morphogenesis by a plant growth promoting rhizobacterium, Streptomyces lincolnensis L4, were investigated from various aspects including microbial physiology, root development and root endophytic microbial community. Strain L4 was isolated from the root associated soil of 7-year plantation of Artemisia annua. Aiming at revealing the promotion mechanism of Streptomyces on root growth and development, this study firstly evaluated the growth promotion characters of S. lincolnensis L4, followed by investigation in the effect of L4 inoculation on root morphology, endophytic microbiota of root system, and expression of genes involved in root development in Arabidopsis thaliana. Streptomyces lincolnensis L4 is able to hydrolyze organic and inorganic phosphorus, fix nitrogen, produce IAA, ACC deaminase, and siderophore, which shaped specific structure of endophytic bacterial community with dominant Streptomyces in roots and promoted the development of roots. From the observation of root development characteristics, root length, root diameter, and the number of root hairs were increased by inoculation of strain L4, which were verified by the differential expression of root development related genes in Arabidopsis thaliana. Genomic traits of S. lincolnensis L4 further revealed its capacity for plant growth promotion in which genes involved in phosphorus solubilization, ACC deamination, iron transportation and IAA production were identified. This root growth promoting strain has the potential to develop green method for regulating plant development. These findings provide us ecological knowledge of microenvironment around root system and a new approach for regulating root development.